The apple GARP family gene MdHHO3 regulates the nitrate response and leaf senescence - Wen, Binbin; Gong, Xingyao; Deng, Wenpeng; Chen, Xiude; Li, Dongmei; Fu, Xiling; Li, Ling; Tan, Qiuping (Frontiers in Plant Science, 2022)
The regulation of plant gene expression by nitrate is a complex regulatory process. Here, we identified 59 G2-like genes in apples by genome-wide analysis. As a member of the G2-like gene family, MdHHO3 is homologous to NIGT1 in maize, and its expression is upregulated under nitrogen supply. The results of DNA binding site analysis and electrophoretic mobility shift assays (EMSA) showed that MdHHO3 binds to the motif-containing GAATC. Furthermore, MdHHO3 binds to its promoter sequence and inhibits its activity. In addition, the overexpression of MdHHO3 in apple calli resulted in less accumulation of nitrate in 35S::MdHHO3-GFP calli and downregulated expression of nitrate transport-related genes but upregulated expression of nitrate assimilation-related genes. Similarly, the expression of nitrate transport-related genes was down-regulated and the expression of nitrate assimilation-related genes was upregulated in MdHHO3 overexpression Arabidopsis and tobacco plants. Interaction experiments showed that MdHHO3 could bind to the promoter of MdNRT2.1 and negatively regulate its expression. Moreover, the exposure of MdHHO3-overexpressing Arabidopsis and tobacco to nitrate deficiency resulted in an early senescence phenotype compared with that observed with the WT plants. These results show that MdHHO3 can not only negatively regulate nitrate accumulation in response to nitrate but also promote leaf early senescence under nitrate deficiency. This information may be useful to further reveal the mechanism of the nitrate response and demonstrates that nitrate deficiency induces leaf senescence in apples.